A strategy to regenerate coked and sintered Ni/Al2O3 catalyst for methanation reaction. (8th November 2018) - Du, Jinping; Gao, Jiajian; Gu, Fangna; Zhuang, Jiahao; Lu, Bin; Jia, Lihua; Xu, Guangwen; Liu, Qing; Su, Fabing
Abstract: Supported Ni/Al2 O3 catalysts are widely used in chemical industries. Regeneration of the deactivated Ni catalysts caused by sintering of Ni nanoparticles and carbon deposition after long-term operation is significant but still very challenging. In this work, a feasible strategy via solid-phase reaction between NiO and Al2 O3 followed by a controlled reduction is developed which can burn out the deposited carbon and re-disperse the Ni nanoparticles well, thus regenerating the deactivated Ni catalysts. To demonstrate the feasibility of this method, Ni catalyst supported on α-Al2 O3 (Ni/Al2 O3 ) for CO methanation reaction was selected as a model system. The structure and composition of the fresh, deactivated and regenerated Ni/Al2 O3 catalysts were comprehensively characterized by various techniques. The reduction and redistribution of Ni species as well as the interfacial interaction between Ni nanoparticles and Al2 O3 support were investigated in detail. It is found that calcining the deactivated Ni/Al2 O3 in air at high temperature can burn out the coke, while the sintered Ni species can combine with superficial Al2 O3 to form a surface NiAl2 O4 spinel phase through the solid-phase reaction. After the controlled reduction of the NiAl2 O4 spinel, highly dispersed Ni nanoparticles on Al2 O3 support are re-generated, thus achieving the regeneration of the deactivated Ni/Al2 O3 . Interestingly, compared with the fresh Ni/Al2 O3 catalyst, the sizes of Ni nanoparticles became even smaller in the regenerated ones. The regenerated Ni/Al2 O3 showed much enhanced catalytic activity in CO methanation and became more resistant to carbon deposition, due to the better dispersed Ni nanoparticles and strengthened interaction between Ni and Al2 O3 support. Our work not only addresses the long existing catalyst regeneration issue, but also provides effective and renewable Ni-based catalysts for CO methanation. Graphical abstract: Highlights: A strategy to regenerate coked and sintered Ni/Al2 O3 catalyst was developed. The strategy was solid-phase reaction followed by a controlled reduction. Solid-phase reaction can burn out the deposited carbon and form NiAl2 O4 phase. Controlled reduction of the NiAl2 O4 can induce re-dispersion of Ni nanoparticles. The regenerated catalyst shows enhanced catalytic activity and stability.